Materiais lignocelulósicos como reforço em tijolo solo-cimento - Sabino, Ticyane Pereira Freire (2019)
The soil-cement bricks are formed by the mixture of soil, cement and water, which after the homogenization pass through the pressing process and has its curing process at room temperature, which makes it an ecological product because it does not burn. The result is a product with good physical-mechanical properties applied in the most diverse works of the world outside. An alternative that has been studied aiming to stabilize the soil used in the manufacture of bricks is the incorporation of lignocellulosic materials, due to the good properties of the material and easy to obtain, since they are produced in large quantity and do not often have a suitable destination. In this context, this study aimed to evaluate different types and percentages of plant particles on the physical, mechan ical, thermal and microstructural properties of soil-cement brick. The chemical properties, retraction, compaction, limits of consistency and granulometry for the soil, the anatomical, chemical and physical properties for the lignocellulosic particles were characterized. Bricks produced with bamboo particles, rice hulls and coffee husks were evaluated in percentages of 1.5 and 3.0%, in addition to a control treatment without particle use. The bricks were pressed in an automatic press to achieve the desired size and were characterized for density, water absorption, porosity, immersion loss, durability test, compressive strength and thermal conductivity. It can be concluded that the bricks produced with 3.0% of rice hull presented the best results compared to the other treatments. The lignocellulosic materials generated significant impacts on the mechanical resistance, water absorption and porosity of the bricks. The inclusion of rice hulls, coffee hulls and bamboo has significantly improved the thermal insulation properties of the hulls.